2020
DOI: 10.1021/acs.iecr.9b06886
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Change CO2 Absorption Using Novel 3-Dimethylaminopropylamine with Primary and Tertiary Amino Groups

Abstract: Phase-change solvents exhibit the promising potential to reduce the regeneration energy for CO 2 capture. In this paper, 3-dimethylaminopropylamine (DMAPA) with intramolecular primary and tertiary amino groups was mixed with solvent NHD and water for phase-change absorption of CO 2 in the model flue gas. The results show that the homogeneous mixture changes into two phases after CO 2 absorption when NHD/H 2 O ranges from 9:1 to 5:5 and 90% of CO 2 is enriched in the lower phase with only 23% of the total volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It was indicated that DMAPA with no hydroxyl group had weaker hydrogen bonding effect, leading to a relatively lower viscosity than MEA in the same volume ratio of NHD and H 2 O. 11 In this work, we report a novel, high performing water-lean solvent with a lower viscosity than those reported water lean solvents in the literature. It is composed of a di-amine, N, N-dimethyl-1, 2-ethanediamine (DMEDA), an organic physical solvent NMP and up to 15% water.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…It was indicated that DMAPA with no hydroxyl group had weaker hydrogen bonding effect, leading to a relatively lower viscosity than MEA in the same volume ratio of NHD and H 2 O. 11 In this work, we report a novel, high performing water-lean solvent with a lower viscosity than those reported water lean solvents in the literature. It is composed of a di-amine, N, N-dimethyl-1, 2-ethanediamine (DMEDA), an organic physical solvent NMP and up to 15% water.…”
mentioning
confidence: 77%
“…8 Thus, organic solvents, for example sulfolane (SFL), N-methyl-2-pyrrolidone (NMP) and poly (ethylene glycol) dimethylether (NHD), with high thermal stability and low vapor pressure were selected to form water-lean systems. SFL, NMP, and NHD based solvents can help lower the high viscosity of water-lean solvents to a certain extent [9][10][11] A relatively low viscosity (3.93 mPa•S) was achieved for the water-lean DETA/SFL solvent at a CO 2 loading of 2.21 mol•L -1 (equal to 1.105 mol CO 2 •mol amine -1 ) at 348 K. 9 7m MEA mixed with NMP and H 2 O in a mass ratio of NMP: H 2 O of 19:1 (equal to 3.5wt. % H 2 O) had a viscosity of 15.4 mPa•S with a CO 2 loading of 0.45 mol CO 2 •mol amine -1 .…”
mentioning
confidence: 99%
“…As a promising alternative, the physical solvent composed of aprotic polar molecules possesses considerably low polarity and heat capacity, which could act as the phase separating agent in the biphasic solvent, including alcohols, ketones, ethers, and their polymers. ,, Compared with the organic small molecules, polyethylene glycol dimethyl ether (NHD) has better chemical stability, low saturated vapor pressure, and low polarity (<10 –23 cm 3 ), which therefore could be considered as an available candidate for phase separation and as a substitute for solvent water. , In addition, use of polyamines, including two or more types of amino group, is an effective route to reconcile the defects of a solvent with a single amino group, which is increasingly adopted during the biphasic solvent design. , However, the interaction mechanism between long-chain polymers and polyamines is obviously complex, which has inevitable influence on the performance of the biphasic solvent. The report about separation dynamics based on bench or large scale separator is relatively deficient, and the cognition of macroscopic upper/lower phase motion is limited on the microscopic intermolecular force.…”
Section: Introductionmentioning
confidence: 99%
“…9,25,26 Compared with the organic small molecules, polyethylene glycol dimethyl ether (NHD) has better chemical stability, low saturated vapor pressure, and low polarity (<10 −23 cm 3 ), which therefore could be considered as an available candidate for phase separation and as a substitute for solvent water. 27,28 In addition, use of polyamines, including two or more types of amino group, is an effective route to reconcile the defects of a solvent with a single amino group, which is increasingly adopted during the biphasic solvent design. 29,30 However, the interaction mechanism between long-chain polymers and polyamines is obviously complex, which has inevitable influence on the performance of the biphasic solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The regeneration energy consumption is 3.6 GJ/t CO 2 at 50 °C. If only the decomposition voltage is calculated (Figure S6), the total energy consumption is only 0.5 GJ/t CO 2 , which is much lower than that in a traditional regeneration process. …”
Section: Resultsmentioning
confidence: 96%